Genome-Wide Identification and Characterization of Fox Genes in the Honeybee, Apis cerana, and Comparative Analysis with Other Bee Fox Genes - Hongyi Nie; Haiyang Geng; Yan Lin; Shupeng Xu; Zhiguo Li; Yazhou Zhao; Songkun Su (International Journal of Genomics)
The forkhead box (Fox) gene family, one of the most important families of transcription factors, participates in various biological processes. However, Fox genes in Hymenoptera are still poorly known. In this study, 14 Fox genes were identified in the genome of Apis cerana. In addition, 16 (Apis mellifera), 13 (Apis dorsata), 16 (Apis florea), 17 (Bombus terrestris), 16 (Bombus impatiens), and 18 (Megachile rotundata) Fox genes were identified in their genomes, respectively. Phylogenetic analyses suggest that FoxA is absent in the genome of A. dorsata genome. Similarly, FoxG is missing in the genomes A. cerana and A. dorsata. Temporal expression profiles obtained by quantitative real-time PCR revealed that Fox genes have distinct expression patterns in A. cerana, especially for three genes ACSNU03719T0 (AcFoxN4), ACSNU05765T0 (AcFoxB), and ACSNU07465T0 (AcFoxL2), which displayed high expression at the egg stage. Tissue expression patterns showed that FoxJ1 is significantly higher in the antennae of A. cerana and A. mellifera compared to other tissues. These results may facilitate a better understanding of the potential physiological functions of the Fox gene family in A. cerana and provide valuable information for a comprehensive functional analysis of the Fox gene family in Hymenopterans.